The Effectiveness of Youtube Channel as Learning Media at Conversation Class - Wulandari, Dewi (Riwayat: Educational Journal of History and Humanities, 2024)
This study aimed to figure out how effective the use of Youtube as a learning media in teaching English for conversation class. The method of the study used was descriptive qualitative. The use of Youtube was considered as a good media to use for teaching English because by Youtube, an English lecturer or teacher can download many interesting videos to present at class. The use of Youtube was also able to avoid the boringness that often comes to the students when learning English. It was proved by the result of this study which revealed that 84% of the students extremely agreed using Youtube as the learning source and media. And 16% of the students agreed using Youtube and considered Youtube as interesting learning source. So, it was concluded that the videos downloaded from Youtube was effective to use in teaching English particularly for speaking